Come si governa la tecnologia digitale? - Califano, Licia (Cultura giuridica e diritto vivente, 2021)
[How to govern digital technology?] Digital technology has brought big advantages for people’s everyday life. Yet, digital world creates many risks for fundamental rights and freedom. The Author analyses the nature and characteristics of those risks, with a special focus on the traditional definition of sovereignty and democracy and the protection of individual liberties and rights, in particular the right to political participation, right to health and to the protection of personal data.